2019
DOI: 10.3390/cells8111457
|View full text |Cite
|
Sign up to set email alerts
|

Natural Histogel-Based Bio-Scaffolds for Sustaining Angiogenesis in Beige Adipose Tissue

Abstract: In the treatment of obesity and its related disorders, one of the measures adopted is weight reduction by controlling nutrition and increasing physical activity. A valid alternative to restore the physiological function of the human body could be the increase of energy consumption by inducing the browning of adipose tissue. To this purpose, we tested the ability of Histogel, a natural mixture of glycosaminoglycans isolated from animal Wharton jelly, to sustain the differentiation of adipose derived mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…It has reported that decreased UCP-1 expression in beige adipocytes from AD-MSCs is associated with mitochondrial ROS accumulation during obesity [ 119 ]. Furthermore, during the differentiation of AD-MSCs into brown-like cells, the expression of UCP-1 increased, differentiated cells show a higher energy metabolism compared to undifferentiated mesenchymal cells, indicating that UCP-1 have a significant role in adipogenic differentiation [ 120 ]. In addition, UCP2 can be stimulated by PGC-1α with mitochondrial biogenesis and respiration, suggesting that PGC-1α is an upstream kinase that regulates UCP2 [ 121 ].…”
Section: The Role Of Mitochondrial Energy Metabolism In the Regulatiomentioning
confidence: 99%
“…It has reported that decreased UCP-1 expression in beige adipocytes from AD-MSCs is associated with mitochondrial ROS accumulation during obesity [ 119 ]. Furthermore, during the differentiation of AD-MSCs into brown-like cells, the expression of UCP-1 increased, differentiated cells show a higher energy metabolism compared to undifferentiated mesenchymal cells, indicating that UCP-1 have a significant role in adipogenic differentiation [ 120 ]. In addition, UCP2 can be stimulated by PGC-1α with mitochondrial biogenesis and respiration, suggesting that PGC-1α is an upstream kinase that regulates UCP2 [ 121 ].…”
Section: The Role Of Mitochondrial Energy Metabolism In the Regulatiomentioning
confidence: 99%
“…The CAM represents a well-established model to investigate several physiological and pathological processes including angiogenesis, tumor growth and dissemination [ 3 , 7 , 8 , 9 ], gas exchange [ 10 ], and ion transport [ 11 ]. The CAM has been also exploited to study material biocompatibility [ 12 ], selective vascular occlusion therapies [ 13 ], drug distribution, and to perform toxicological analyses [ 14 , 15 ]. The easy access for experimental manipulation and the low cost make this system a valid alternative to other in vivo models [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue covers research articles investigating various adipose tissues as a source for ASC isolation [ 1 , 2 , 3 ], specific cultures methods to enhance proliferation or viability [ 4 , 5 , 6 , 7 ], and the differentiation capacity [ 8 , 9 , 10 , 11 , 12 ]. Furthermore, other studies highlight aspects of various diseases [ 13 , 14 ], the immunosuppressive potential of ASCs and their derivates [ 15 ] or the in vivo tracking of transplanted ASCs [ 16 ].…”
mentioning
confidence: 99%
“…Their data indicated that measuring these compounds could be a useful, non-invasive tool for the metabolic monitoring of cells in vitro. Di Somma and co-workers tested the ability of Histogel, a natural mixture of glycosaminoglycans, to sustain the differentiation of ASCs into brown-like cells and brown adipose tissue [ 12 ]. A study by Plava and co-workers identified that ASCs are permanently altered in the presence of tumor breast tissue and have the potential to increase tumor cell invasive ability through the activation of epithelial-to-mesenchymal transition in tumor cells [ 13 ].…”
mentioning
confidence: 99%